44.4k views
9 votes
What is the solution to the equation 4x-6= 10x-3?
X=-2
O X=2
O X=
O X= 2

2 Answers

4 votes

Answer:

the first one x = -2

Explanation:

Let's solve your equation step-by-step.

4x−6=10x−3

Step 1: Subtract 10x from both sides.

4x−6−10x=10x−3−10x

−6x−6=−3

Step 2: Add 6 to both sides.

−6x−6+6=−3+6

−6x=3

Step 3: Divide both sides by -6.

User Yusef
by
4.6k points
8 votes

Answer:

x = -1/2

Explanation:

4x - 6 = 10x - 3

+6 +6

4x = 10x + 3

-10x -10x

-6x = 3

3 / -6 = -1/2

User Alecbz
by
4.5k points